Guide to interventional radiology in cats and dogs. Issue 9 (13th November 2020) - Kent, Andrew
Abstract : Background: Interventional radiology covers a group of procedures that are performed under imaging guidance, including fluoroscopy, endoscopy, ultrasound and computed tomography. The procedures are minimally invasive and tend to use percutaneous access or natural orifices to access the target area and deliver a treatment. Aim of the article: This article provides a review of the currently performed interventional radiology procedures, including cardiorespiratory, urogenital, hepatobiliary/gastrointestinal and vascular techniques.